Snapshot of the Quality of Public Service in Supporting the Integrity Zone - Waode Eti Hardiyanti; Sri Rawanti; Endah Setiyowati; Nur Luthfi Ardhian (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2023)
Higher Education is one government institution that implements the bureaucratic reform program through the Zone of Integrity (ZI) development program. ZI planning towards a Corruption Free Area (known as WBK) and a Clean and Serving Bureaucratic Region (known as WBBM) was conducted at the Faculty of Education (FIP) of the Universitas Negeri Gorontalo (UNG), which is committed to implementing WBK/WBBM. In implementing ZI, synergy, and commitment are needed between the leadership and the entire academic community. One of the components in realizing ZI is the optimal quality of public services for both internal and external parties. The research used survey that sent to 200 participants. Then, 15 questionnaires were constructed and the results were analyzed. The survey results related to internal public services in supporting the implementation of the integrity zone of the Faculty of Education, State University of Gorontalo, are in the satisfactory category as seen from 15 indicators of public services, nine items in the satisfactory category, followed by five very satisfactory categories. This shows that the public services provided are in the good category, but improvements in several aspects must still be carried out.